Endodontic misdiagnosis of periapical central giant cell granuloma: Report of case with 2 years of follow-up - Rahul Kumar; Neha Khambete (Wolters Kluwer Medknow Publications, 2012)
Central giant cell granuloma is considered as reactive lesion of jaws possibly to intramedullary hemorrhage or trauma. It may manifest as radiolucencies anywhere in the mandible or maxilla. In rare cases, it can appear as a localized periapical area and mimic an endodontic lesion. This report presents a case where central giant cell granuloma was misdiagnosed as a periapical cyst in 20-year-old male and was treated by conventional endodontic treatment. However the lesion was refractory to endodontic treatment and proved to be central giant cell granuloma after surgical intervention and histopathological examination. The purpose of this case report is to emphasize on periodic follow-up of periapical lesions after endodontic treatment and surgical intervention if required.